Pop Up Book Kubus dan Balok Untuk Siswa SMP - Kusno Kusno; Muvida Indah Kusuma (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
The research aims to construct learning media for pop up books on cube and block materials that are suitable for use in junior high school students. This research is a development study using a modified 4-D model that is Define, Design, Develop and Deseminate from Thiagarajan. The subject of the material developed in this study was cube and beam class VIII material with a class VIII trial subject of SMPN 1 Sumbang. The results showed that the learning media pop up book was very valid (3.57) according to the validator, the teacher's response was very good (3.31) and student responses were good (3.29)